EFEKTIFITAS MEDIASI DI PENGADILAN AGAMA SUMBER CIREBON (KAJIAN PERATURAN MAHKAMAH AGUNG NOMOR 1 TAHUN 2016) - Abid Sohih; Ach Faisol; Nur Hasan (Prodi Ahwal syakhshiyyah Fakultas Agama Islam UNISMA, 2020)
AbstractMediation is a model of problem solving through deliberation to obtain the agreement of the parties with the assistance of the mediator or a judge. This writing aims to determine the effectiveness of mediation in Sumber Cirebon Religious Court Number 1 of 2016. This type of research is a field of study, the type of research used is descriptive research qualitative, mainly by describing a state of subject or object of research. Then the data collection methods used are interviews, observation and documentation. Then the data processing and analysis techniques used by using that the effectiveness of mediation in Sumber Cirebon Religious Court based on the review of Supreme Court Regulation Number 1 of 2016 have not been effective, this is because the parties do not have good faith and in each mont there are approximately 700 cases that go to court religious sources. However, the implementation of Supreme Court Regulation Number 1 in 2016 at the source religious court has been effective and has been implemented since March 2016.Keywords: Effectiveness, Mediation, Supreme Court Regulation Number 1 in 2016.